2007
DOI: 10.1021/ol063143k
|View full text |Cite
|
Sign up to set email alerts
|

A Formal Synthesis of Psymberin

Abstract: A formal synthesis of psymberin (irciniastatin A) is presented. Notable features of the synthesis include the chemo-, regio-, and stereoselective oxidation of a 1,3-disubstituted allene, a configuration-dependent spirodiepoxide opening, the efficient syntheses of functionalized trans-2,6-disubstituted pyrans, and the union of a highly functionalized aldehyde with a pentasubstituted aryl homoenolate to give a dihydroisocumarin. [structure: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 36 publications
1
36
0
6
Order By: Relevance
“…With this overview in mind, disconnection of the amide bond in (+)- 1 (Scheme 1), as with the earlier reported syntheses, 5,7,8 leads to a side chain acid ( 2 ) and amide coupling precursor ( 3 ), the latter bearing a Teoc-protected N , O -aminal. We envisioned that elaboration of the N , O aminal could be achieved in a highly stereoselective fashion exploiting a late-stage Curtius rearrangement similar to that developed and employed in our total syntheses of (+)- dactylolide and (+)-zampanolide.10 Further disconnection at the C(16,17) bond leads to aldehyde 4 and 2,6- trans tetrahydropyran 5 , which would be joined via a 1,4- substrate controlled boron-mediated aldol reaction to control the configurations of the C(16,17) stereogenic centers.…”
supporting
confidence: 57%
“…With this overview in mind, disconnection of the amide bond in (+)- 1 (Scheme 1), as with the earlier reported syntheses, 5,7,8 leads to a side chain acid ( 2 ) and amide coupling precursor ( 3 ), the latter bearing a Teoc-protected N , O -aminal. We envisioned that elaboration of the N , O aminal could be achieved in a highly stereoselective fashion exploiting a late-stage Curtius rearrangement similar to that developed and employed in our total syntheses of (+)- dactylolide and (+)-zampanolide.10 Further disconnection at the C(16,17) bond leads to aldehyde 4 and 2,6- trans tetrahydropyran 5 , which would be joined via a 1,4- substrate controlled boron-mediated aldol reaction to control the configurations of the C(16,17) stereogenic centers.…”
supporting
confidence: 57%
“…53 Advanced allene 95 was subjected to DMDO oxidation to give the intermediate 1,4-dioxaspiro[2.2]pentane, which cyclized to dihydropyranone 96 upon the addition of methanol. Dihydropyranone 96 was transformed into a known intermediate in the synthesis of psymberin 97 .…”
Section: 1 4-dioxaspiro[22]pentanesmentioning
confidence: 99%
“…Through the total synthesis of several diastereoisomers consistent with partially assigned structures of 1 and 2 , our group concluded that psymberin and irciniastatin are actually identical compounds. 6 Several other total syntheses, 7 formal syntheses, 8 fragment syntheses, 9 as well as analog syntheses, 10 have appeared during recent years. A combined supply of natural psymberin and material prepared by our group enabled further in vivo evaluation by the NCI Developmental Therapeutics Program, which indicated encouraging therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%